TINJAUAN EPISTEMOLOGI TERHADAP MODEL PROBLEM BASED LEARNING GUNA MEWUJUDKAN DEEP LEARNING PADA SISWA SEKOLAH DASAR - Nurul Fauziah; Rahmi Susanti; Umi Chotimah; Yosef (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Education in elementary schools today no longer focuses solely on memorization but needs to lead to a deeper understanding of concepts. This aligns with the spirit of the Independent Curriculum, which emphasizes meaningful learning for students. This study examines the validity of Problem-Based Learning (PBL) as a key strategy in elementary schools, critically analyzing it through a constructivist epistemology lens. Using a literature review method, this research examines the suitability of the PBL structure to students' cognitive development. The results indicate that Problem-Based Learning (PBL) aligns with the thinking styles of elementary school students at the concrete operational stage, as learning begins with real-life problems relevant to their lives (Piaget), while group interactions stimulate the construction of social knowledge (Vygotsky). Furthermore, this study highlights the urgency of integrating Flipped Learning as a technological scaffold to effectively utilize face-to-face time for higher-order thinking activities. It can be concluded that PBL can be an appropriate approach to help students achieve deeper understanding in learning.